(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper is a review on calculation of Bit Error Rate/Symbol Error Rate of Wireless mesh networks. WMNs have emerged as a flexible, reliable and cost effective way of providing broadband internet access over wide areas through multi hop communication. In this work the BER (Bit Error Rate) performances is shown analytically and by means of simulation for Rayleigh fading multipath channels and AWGN Gaussian channel. This work focuses on error performance of phase modulation schemes in different channel conditions and on the method to reduce bit error rates.